Flower-like NiCo2O4 from Ni-Co 1, 3, 5-benzenetricarboxylate metal organic framework tuned by graphene oxide for high-performance lithium storage. (20th July 2018) - Gan, Qingmeng; Liu, Bingjun; Zhao, Kuangmin; He, Zhen; Liu, Suqin
Abstract: Three-dimensional (3D) flower-like NiCo2 O4 (F-NiCo2 O4 ) is synthesized through using graphene oxide (GO) as "designer additives" to induce Ni-Co 1, 3, 5-benzenetricarboxylate metal-organic framework (Ni-Co-BTC MOF) from nanoparticles to form nanoneedles, and then further self-assembles to a 3D flower-like morphology. A possible process of morphological change is described in detail according to the changing amount of GO and reaction time. The as-prepared unique structure constructed by ultrafine subunits exhibits a high specific surface area (152.8 m 2  g −1 ) and plentiful mesopores. As an anode in lithium-ion battery, F-NiCo2 O4 shows a high capacity of 1167 mA h g -1 at a current density of 200 mA g −1 and even maintains 333 mA h g -1 at a high rate of 5000 mA g −1 . Moreover, the 3D flower-like F-NiCo2 O4 remains a high capacity of 1067 mA h g -1 at 1000 mA g −1 after 400 cycles. The novel method in this work paves a new way to form 3D structure by using GO to induce MOF aggregation, which may be extended to preparing other metal/metal oxides materials for electrochemical energy-storage systems.